# Answer to Question #44096 in Complex Analysis for ch

Question #44096

hey, i wanna know step by step how sqrt(-2i) = sqrt(2)*e^(-i*pi/4) = (1-i)

is it necessary to change it to polar form first to get to 1-i ?

and when solving w^2= (-1+sqrt3 i)/2 how does the argument get tan^-1(-sqrt3)=2pi/3

shouldn´t it be tan^-1(-2sqrt3/2) if the formula for argument is arctan(y/x) ?

thnx

is it necessary to change it to polar form first to get to 1-i ?

and when solving w^2= (-1+sqrt3 i)/2 how does the argument get tan^-1(-sqrt3)=2pi/3

shouldn´t it be tan^-1(-2sqrt3/2) if the formula for argument is arctan(y/x) ?

thnx

Expert's answer

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment